Developmental validation of Oxford Nanopore Technology MinION sequence data and the NGSpeciesID bioinformatic pipeline for forensic genetic species identification. (July 2021) - Vasiljevic, Nina; Lim, Marisa; Humble, Emily; Seah, Adeline; Kratzer, Adelgunde; Morf, Nadja V.; Prost, Stefan; Ogden, Rob
Abstract: Species identification of non-human biological evidence through DNA nucleotide sequencing is routinely used for forensic genetic analysis to support law enforcement. The gold standard for forensic genetics is conventional Sanger sequencing; however, this is gradually being replaced by high-throughput sequencing (HTS) approaches which can generate millions of individual reads in a single experiment. HTS sequencing, which now dominates molecular biology research, has already been demonstrated for use in a number of forensic genetic analysis applications, including species identification. However, the generation of HTS data to date requires expensive equipment and is cost-effective only when large numbers of samples are analysed simultaneously. The Oxford Nanopore Technologies (ONT) MinION™ is an affordable and small footprint DNA sequencing device with the potential to quickly deliver reliable and cost effective data. However, there has been no formal validation of forensic species identification using high-throughput (deep read) sequence data from the MinION making it currently impractical for many wildlife forensic end-users. Here, we present a MinION deep read sequence data validation study for species identification. First, we tested whether the clustering-based bioinformatics pipeline NGSpeciesID can be used to generate an accurate consensus sequence for species identification. Second, we systematically evaluated the read variation distribution around the generated consensus sequences to understand what confidence we have in the accuracy of the resulting consensus sequence and to determine how to interpret individual sample results. Finally, we investigated the impact of differences between the MinION consensus and Sanger control sequences on correct species identification to understand the ability and accuracy of the MinION consensus sequence to differentiate the true species from the next most similar species. This validation study establishes that ONT MinION sequence data used in conjunction with the NGSpeciesID pipeline can produce consensus DNA sequences of sufficient accuracy for forensic genetic species identification. Highlights: Validation results demonstrate reliability of ONT MinION TM consensus sequences for forensic species identification MinION. Maximum MinION TM replicate sequence deviation from Sanger control data was 1 base over the 420 bp sequence length 1 420 b length. This is the first developmental validation of MinION TM sequencing and bioinformatic processing for forensic DNA barcoding MinION.